Electrical response of β-PVDF in a constant uniaxial strain rate deformation - Sencadas, Vítor João Gomes Silva (2004)
The microstructure of β-PVDF has great influence on its piezo- and pyroelectric responses. The microstructure of β-PVDF drastically changes upon a mechanical deformation perpendicular to the preferred chain orientation, mainly above the yielding point. The voltage (open-circuit response) developed in β-PVDF films was monitored while the material is subjected to a constant strain rate program